Risk of skin cancer in patients with vitiligo in Denmark: A nationwide cohort studyCapsule Summary - Mads Gustaf Jørgensen, MD; Navid Mohamadpour Toyserkani, MD, PhD; Alexander Egeberg, MD, PhD; Jens Ahm Sørensen, MD, PhD (JAAD International, 2020)
Background: Vitiligo is a depigmentation disorder associated with genetic loss of melanocytes and decreased melanin synthesis. The current literature is conflicting in regard to vitiligo patients' risk of cutaneous malignant melanoma and keratinocyte cancer. Objective: To investigate the risk of cutaneous malignant melanoma and keratinocyte cancer in vitiligo patients. Methods: We conducted a population-based study, including 2,339 subjects with a first-time vitiligo diagnosis between 1994 and 2017 and 23,293 age- and sex-matched (1:10) controls. To address surveillance bias, we included 12,380 subjects with a first-time diagnosis of lichen planus. Results: Age was the only significant factor for cutaneous malignant melanoma in comparison of vitiligo with controls and lichen planus (hazard ratio 1.04, 95% confidence interval [CI] 1.03-1.05; and hazard ratio 1.02, 95% CI 1.01-1.04, respectively). Similarly, age was a significant factor for keratinocyte cancer in comparison of vitiligo with controls and lichen planus (hazard ratio 1.07, 95% CI 1.06-1.07; and hazard ratio 1.06, 95% CI 1.05-1.07). Male sex was an additional factor for keratinocyte cancer in comparison of vitiligo with lichen planus (hazard ratio 1.38; 95% CI 1.09-1.75). Phototherapy did not increase the risk of receiving a diagnosis of cutaneous malignant melanoma or keratinocyte cancer in the vitiligo cohort. Conclusion: We observed no significant difference in cutaneous malignant melanoma or keratinocyte cancer risk among vitiligo subjects. Phototherapy use was not associated with a higher skin cancer risk in vitiligo compared with other skin diseases.